Peningkatan Kinerja Perawat dalam Pendokumentasian Asuhan Keperawatan Melalui Supervisi Kepala Ruang di Instalasi Rawat Inap Rumah Sakit Royal Progress Jakarta - Anah Marwanah; Zakiyah; Siswani Marianna (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Supervision in documenting nursing care is one of the factors affecting the performance of a nurse in documenting nursing care. The research objective was to determine the effect of headroom supervision on the performance of nurses in documenting nursing care in the inpatient installation of the Royal Progress Jakarta Hospital. This study used a pre-experimental design method in the form of a pre-post test design without control group. The study population was all nurses who documented nursing care in the inpatient room of the Royal Progress hospital with a total of 55 nurses. The research sample consisted of 55 respondents who were taken using total sampling technique. Data collection using primary data through questionnaires, then analyzed univariate and bivariate. The results obtained by nurses in the Inpatient Installation of Royal Progress Jakarta Hospital who performed well before supervision were carried out as many as 45 (81.8%) respondents, while nurses who performed well after supervision were 49 (89.1%) respondents. The results of the bivariate analysis obtained a p-value of 0.002, which means that there is an effect of headroom supervision on the performance of nurses in documenting nursing care at the Inpatient Installation of the Royal Progress Jakarta Hospital in 2020. Suggestions from this study are that nurses are expected to be consistent in providing excellent service to patients there must be supervision in accordance with existing procedures so that good work results are created and can become a standard for better performance progress in documenting nursing care.